Maldives Systematic Country Diagnostic Update - World Bank (World Bank, Washington, DC, 2021)
Maldives is the smallest yet most densely populated country in South Asia. Endowed with an extremely rich and diverse marine ecological system, Maldives has been able to develop a successful high-end tourism sector. Tourism continues to be the main engine of growth, but there are limited interlinkages between the high-end tourism sector and the local economy. This document builds on the findings in the 2015 Systematic Country Diagnostic, providing an in-depth analysis on labor market outcomes and spatial disparities.